RESEÑA de: Alvarado Planas, Javier; Montes Salguero, Jorge; Pérez Marcos, Regina; Sánchez González, M.ª Dolores. "Manual de Cultura Europea en España". Editorial Sanz y Torres. UNED, Madrid, 2016, 294 págs - Muñoz Catalán, Elisa (Revista de Derecho de la UNED (RDUNED), 2018)
-